2012
DOI: 10.1007/s11095-012-0914-2
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Formulations for Stabilizing IgMs During Physical Stress and Long-Term Storage

Abstract: A long-term stabilizing formulation for 8 IgMs was found comprising 20% sorbitol and 1 M glycine at pH 5.0-5.5 which may have broad utility for other IgMs. Formulation development using DSC and accelerated storage was evaluated in this study and may be used for other proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 44 publications
2
17
0
Order By: Relevance
“…The protein form factor is the Fourier transform of the pair correlation of the crystallographic data of cutinase. The pair correlation was computed by taking into account all sites as possible sources of scattering (20)(21)(22).…”
Section: Methodsmentioning
confidence: 99%
“…The protein form factor is the Fourier transform of the pair correlation of the crystallographic data of cutinase. The pair correlation was computed by taking into account all sites as possible sources of scattering (20)(21)(22).…”
Section: Methodsmentioning
confidence: 99%
“…Another study examined the stability of eight mouse mAbs and concluded that DSC was predictive of accelerated and long term storage for six out eight of the mAbs studied 39 . Cases in which conformational stability did not clearly predict physical stability of mAbs have also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical and clinical studies have underscored the efficacy against various infectious agents of polyclonal IgM-enriched preparations administered by the systemic route (22)(23)(24)(25)(26). Similar to SIgA, SIgM can be seen as a valid candidate immunoglobulin for mucosal application, given its ability to bind antigens with strong avidity, its potential to ensure long term protection (27), its capacity to survive low pH conditions (28), as well as its resistance to proteases (29). We have demonstrated recently that human plasma can serve as a source of polyreactive, polymeric IgA (pIgA) and IgM to generate secretory-like IgA and IgM Abs, the natural molecular form found in secretions.…”
mentioning
confidence: 99%